First CH3D detection in Class 0/I proto-brown dwarfs: constraints on CH4 abundances. Issue 1 (27th January 2022) - Riaz, B; Thi, W-F
ABSTRACT: We report the first detection in the JK = 10 –00 rotational transition line of CH3 D towards three Class 0/I proto-brown dwarfs (proto-BDs) from IRAM 30-m observations. Assuming a rotational temperature of 25 K, the CH3 D abundances (relative to H2 ) are in the range of (2.3–14.5) × 10 −7 . The CH4 abundances derived from the CH3 D abundances and assuming the DCO + /HCO + ratios are in the range of (0.05–4.8) × 10 −5 . The gas-phase formation of CH3 D via CH2 D + is enhanced at high densities of 10 8 –10 10 cm −3 and our observations are likely probing the innermost dense and warm regions in proto-BDs. Thermal and/or non-thermal desorption can return the CH3 D and CH4 molecules formed at an early stage on grain surfaces to the gas-phase. The gas-phase abundances are indicative of warm carbon-chain chemistry in proto-BDs where carbon-chain molecules are synthesized in a lukewarm (∼20–30 K) region close to the central source.